MOTIF SOSIAL TAHLILAN MASYARAKAT MUHAMMADIYAH PLOSO, SURABAYA TIMUR - Aprillia, Fransisca (Paradigma, 2022)
In contrast to Muhammadiyah members who reject the tahlilan tradition, the majority of the people of Muhammadiyah Ploso still believe in and maintain the tahlilan tradition as a hereditary heritage. The purpose of this study is to describe the typology of the Muhammadiyah Ploso community, to describe the practice of tahlilan from the Muhammadiyah Ploso community, and to describe the social motives of the tahlilan community of the Muhammadiyah Ploso community. The theory used in this research is Alfred Schutz's perspective of phenomenology. This study uses a qualitative method with a phenomenological approach proposed by Alfred Schutz. Data collection in this study was carried out using semi-involved observation techniques, semistructured interviews, and documentation. The results of this study indicate that; First, the typology of the Muhammadiyah Ploso community consists of four variants, namely Al-Ikhlas, Kiai Dahlan, Muhammadiyah-NU (Munu), and MarhaenisMuhammadiyah (Marmud). Second, the practice of tahlilan of the Muhammadiyah Ploso community consists of three concepts, namely association, content of tahlil reading, and banquet. Third, the underlying motive for the Muhammadiyah Ploso community to carry out tahlilan is a family background that is bound by Javanese tradition, beliefs about values in tahlilan, and an environment where the majority still maintains the tahlilan tradition. Meanwhile, the motive for the Muhammadiyah Ploso community to carry out tahlilan is a form of cultural expression, social solidarity, a form of doing good and being devoted to parents, hoping for self-safety, social harmony, and a form of tolerance for people who still carry out tahlilan. Keywords: Muhammadiyah community; social motives; tahlilan